Chip Design of PTP Time Synchronization for Industrial IoT - Yee-Shao Chen; Yuan-Sun Chu; da-Wei Lo; Yen-Ting Chiang; Ting-Chao Hou (IEEE Access)
The world is currently in the midst of the fourth industrial revolution (also known as Industry 4.0). Its core concept is to apply technologies such as computer networking, big data, artificial intelligence and cloud services to manufacturing. Because information between each other must be communicated immediately to ensure that each device in the system performs work at an accurate time. Therefore, each device in the computer network needs a precise reference time, and high-precision time synchronization technology plays an indispensable role. After a detailed study of the IEEE 1588 protocol, this paper found that the main sources of time errors are frequency changes caused by the temperature characteristics and aging of the crystal oscillator, the uncertainty of network protocol stacking delay, and the queuing delay caused by packets. In order to improve time accuracy and reduce delays caused by network protocol stacking, this study designed the chip on the data link layer and optimized the original IEEE 1588 protocol. These optimization methods include compensating clock skew and removing run-trip delay Time is too large mechanism. Finally, this paper designed an IEEE 1588 protocol chip located on the data connection layer based on these methods, and achieved an operating frequency of 434MHz under the 45nm process. Experimental results show that the time synchronization value can be maintained within ±26 nanoseconds. This can not only effectively reduce the delay caused by network protocol stacking, but also meet the requirements for time synchronization accuracy of the modern industrial Internet of Things.